Flexibilidade na dieta alimentar da formiga granívora Pogonomyrmex naegelii (Forel, 1878) em habitat fortemente sazonal - Borges, Carla Cristina Rodrigues (2016)
Ants establish importants ecological interactions with plants, and seed predation is one of the basic types of antagonistic interactions. Seed-harvester ants plays an important ecological role as seed consumers, may promote qualitative changes in community structure and ecosystem functioning. Furthermore, fluctuations in composition and abundance of species of plants that provide seeds to the ants influence the diet of these insects. Pogonomyrmex naegelii is a seedharvester ant widely distributed in South America. In Brazil, occurs in the Cerrado, where their interactions are considered an important component of the trophic web. Fieldwork was conducted in a Brazilian savanna area in Uberlândia city, where it was intended to analyze the feeding flexibility and consumption of seeds and non-seeds items, which plant species are collected by ants, which species grow near to nests and when their seeds are available and selective seed consumption of certain species of plants. Thus, we hypothesized that there is a negative relationship between the diversity of seeds and non-seeds (e.g., arthropods, leaves, flowers) consumed. Due to the strong seasonality of the Cerrado, the plants should produce seeds only in specific periods of the year. Thus, ants should consume several plant species throughout the year, but it is expected that some are eaten more than others. We also expected to find a high wealth of plants close to their nests, but in fact, few species should be consumed. Further, it is expected that occurs selectivity in the collection of food items. For this, colonies of P. naegelii were monitored in order to obtain data on the composition of the diet of these ants, we also sampled species of plants near to the ant’s nests to obtain composition and abundance of plants. There were differences in foraging by P. naegelii dependent on the seasonality of the Cerrado. Seed collection was higher in the dry season, however, despite the diet become more balanced in the rainy season, with ants consuming higher proportions of other items than seeds, seeds were the items more collected by the ants, independently of the season. Different species of plants produced seeds in specif periods of the year, and there was a negative relationship between seed and non-seed diversity consumed by the ants. Moreover, despite the high proportion of plants found close to the nest just a few were consumed, occurring selectivity in plant food consumption. This variation in the diet reflecting the abundance of available resources is observed in seed-harvester ants, supporting the idea that selectivity should be decreased under conditions of low food abundance through the incorporation of various less preferred items, the prediction of optimal foraging theory. Thus, in P. naegelii changes in abundance and composition of plants species can directly influence the diet of this ant.